IMPLEMENTASI FRAMEWORK MVC PADA SISTEM INFORMASI AKADEMIK DI STMIK YADIKA BANGIL - Wildan Mualim, Gema Ulama Putra (SPIRIT, 2018)
In web application development, there are no principal rules or standards. This caused a problem when the application is developed by more than one programmer as because it will be difficult when integrating the whole project together or for further development. Just as in Academic Information Systems in STMIK Yadika Bangil, which is built from scratch without following any architectural standards. It's neccessary to implement an MVC framework to the systems to make the code maintainable and ease the integration and database management. The implementation of MVC framework can ease development process and increase development speed by reducing repetitive tasks.Keywords : Framework, MVC, Website